Effects of e-marketing on customers patronage of commercial banks, a study of Guaranty Trust Holding Company PLC, Lagos - Abdulazeez Olamide, Abdulquadri (2022)
This study examined the effects of E-marketing on customers’ patronage of commercial banks a study of Guaranty Trust Bank (GTBank) PLC, Lagos. The study adopted quantitative research design and the sources of data for this study were purely primary and secondary and a sample size of 385 customers of GTBank Plc, in Akoka area of Yaba Local Government, Lagos state were selected through a convenience sampling technique. The data were analyzed and descriptive statistics (mean and median), regression analysis and analysis of variance were used to provide answers to the research questions and test hypotheses. The study revealed that there is a direct nexus between the use of internet banking, and increase in customer patronage of GTBank, Plc, Lagos. Furthermore, a positive relationship was established between the use of USSD codes and quick service delivery of GTBank, Plc, Lagos. The study therefore conclude that E-marketing influences customers’ patronage of GTBank PLC, Lagos and it was recommended that GTBank PLC, Lagos should continue the utilization of its E-marketing components (i.e. Internet banking, and USSD codes) as this assist in serving their customers better through quick service delivery and also increases the utility enjoyed which encourage frequent patronage. Future researchers can make research on same topic but increasing the scope to other commercial banks in Nigeria for better comparison.